2021
DOI: 10.3389/fpubh.2021.589734
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' Knowledge, Attitudes, and Practices Toward Medicine Price Transparency at Private Healthcare Setting in Malaysia

Abstract: Background: Medicine price transparency refers to the practice of making prices available to consumers for them to identify, compare, and select the medicine that provides the desired value. This study aimed to evaluate consumer knowledge, attitudes, and practices regarding Malaysia's medicine price transparency initiative, as well as factors that may influence related good consumer practices in private healthcare settings.Methods: A cross-sectional, self-administered survey was conducted between May and July … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…This is particularly relevant for an on-site visit, especially since price transparency in German CPs is low due to the lack of mandatory price labeling [ 103 ] and due to price communication that usually takes place only shortly before drug dispensing [ 70 ]. Affected individuals should therefore be encouraged by public campaigns to actively inquire about and compare prices—as simulated in this MC study—and then subsequently make appropriate cost–benefit trade-offs [ 104 ]. However, this MC study showed that some CPs—despite being asked—did not provide prices (e.g., due to an exit).…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly relevant for an on-site visit, especially since price transparency in German CPs is low due to the lack of mandatory price labeling [ 103 ] and due to price communication that usually takes place only shortly before drug dispensing [ 70 ]. Affected individuals should therefore be encouraged by public campaigns to actively inquire about and compare prices—as simulated in this MC study—and then subsequently make appropriate cost–benefit trade-offs [ 104 ]. However, this MC study showed that some CPs—despite being asked—did not provide prices (e.g., due to an exit).…”
Section: Discussionmentioning
confidence: 99%
“…For variables measured by multiple items, a composite index was obtained from the mean to indicate the score of each variable. Using Bloom’s cutoff, respondents were categorized as good practices when their adherence practices score exceeded 3 (more than 60% on a 5-point Likert scale) and poor practices otherwise ( 31 ).…”
Section: Methodsmentioning
confidence: 99%